Thoracic parietal defect plasties: Comparative study of the use of dura mater and synthetic meshes - Sanguinetti, Julio; Sorondo, Martín; Fernández, Miguel; Penco, Ernesto (Cirugía del Uruguay, 1975)
An experimental study was performed on 20 dogs, comparing the usefulness of synthetic meshes and human dura mater in the repairing of thoracic wall defects. The results were satisfactory with both malerials, with sorne advantages when using human dura mater: more complete and faster pulmonary re-expansion.